PEMAHAMAN KONSEP GRUP MAHASISWA CALON GURU MATEMATIKA DENGAN KEMAMPUAN MATEMATIKA TINGGI - Pramasdyahsari, Agnita Siska; Rubowo, Maya Rini (Universitas Insan Budi Utomo, 2020)
The study aims to describe the understanding of group concepts in prospective mathematics teacher with high mathematical abilities. This research is a descriptive qualitative research, with a research subject is a prospective mathematics teacher who have taken group theory courses. The subjects were selected according to the criteria of having high mathematical abilities based on mathematical ability tests, having good communication skills and being able to explain. Data collection was carried out through providing group concept understanding tests followed by interviews. Written tests and interviews were conducted twice for the purposes of triangulating data through time triangulation. Regarding to the discussion section, it can be summarized that subjects with high mathematical abilities can define and show a group fulfilling the traits in detail.